Pengaruh Struktur Modal, Kinerja Keuangan dan Ukuran Perusahaan terhadap Nilai Perusahaan - Choirunissa, Syifa; Ratnasari, Fina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The value of a company is a key indicator of its success and sustainability, often influenced by various internal factors such as capital structure, financial performance, and company size. This study aims to examine the effect of capital structure, financial performance, and company size on firm value. The research focuses on companies in the Consumer Non-Cyclicals sector, specifically the Food and Beverage subsector, listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach with a causal associative method was employed in this study. The data used are secondary in nature, consisting of financial reports obtained from the official IDX website (www.idx.co.id), IDN Financials, and the respective company websites. A total of 100 data points were selected using purposive sampling. The data were analyzed using multiple regression analysis, including descriptive statistics, panel regression model testing, classical assumption tests, and hypothesis testing. All data processing was conducted using EViews 13. The results indicate that capital structure, financial performance, and company size each have a significant effect on firm value. Furthermore, these three variables also simultaneously influence company value. The findings suggest that internal financial decisions and company scale play an essential role in determining firm valuation, providing useful insights for stakeholders and management in strategic planning.